Both Notch1 and its ligands in B cells promote antibody production. (November 2017) - Zhu, Gaizhi; Wang, Xiaoqian; Xiao, He; Liu, Xiaoling; Fang, Ying; Zhai, Bing; Xu, Ruonan; Han, Gencheng; Chen, Guojiang; Hou, Chunmei; Shen, Beifen; Li, Yan; et al.
Highlights: Both Notch1 and its ligands Dll1 and Jag1 express in B cells. Notch1 knock-down in B cells reduces antibody production in LPS-stimulated B cells. LPS-activated splenocytes with Notch1-knocked-down B cells produce normal antibody. Notch1 knock-down in B cells does not affect antibody production in EAE mice. Notch1 promotes Notch1-knocked-down B cells to produce antibody. Abstract: Notch1 signaling regulates B and T lymphocyte development and also in vitro promotes antibody secretion upon B cell activation. However, it is still unclear about the role of Notch1 in antibody production upon in vitro and in vivo mixture lymphocytes activation. We first showed that Notch1 expressed in LPS-activated CD19 hi B cells and CD19 cre mediated Notch1 knock-down in LPS-activated B cells. Furthermore, we demonstrated that Notch1 knock-down in B cells reduced antibody production in LPS-stimulated B cells but did not affect antibody production in LPS-stimulated splenocytes and in experimental allergic encephalomyelitis (EAE) mice. Importantly, Notch1 ligands Dll1 and Jag1 expressed in B cells and pre-coated Notch1 protein promotes Notch1-knocked down B cells to produce antibody in LPS-stimulated B cells suggesting that Notch1 in other cells may promote antibody production by binding its ligands Dll1 and Jag1 in B cells. Together, our results suggest that both Notch1 and its ligands in B cells play an important role in antibody production.